2013
DOI: 10.1039/c3ta12480k
|View full text |Cite
|
Sign up to set email alerts
|

High flux ethanol dehydration using nanofibrous membranes containing graphene oxide barrier layers

Abstract: In this study, pristine multilayered graphene oxide (GO) was coated by established methods onto a thinfilm nanofibrous composite (TFNC) mat to form a high flux membrane for ethanol dehydration. The thickness of the GO layer was controlled from 90 to 300 nm by taking advantage of the self-assembly behavior of GO sheets. The low transfer barrier of the TFNC mat provides a distinct advantage due to its large bulk porosity (80%) with fully interconnected pore structures. Ethanol dehydration experiments showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(36 citation statements)
references
References 24 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…To avoid swelling of GO membranes, chemical bonding was introduced into GO membranes to “lock” GO flakes in the adjacent layers . GO membranes can also be stabilized using cross‐linking agents, such as multivalent ions, diamine, or dyadic monomers . Via a LBL deposition technique, TMC was used to cross‐link adjacent GO flakes .…”
Section: Go‐based Membranes With Lamellar Structurementioning
confidence: 99%
“…To avoid swelling of GO membranes, chemical bonding was introduced into GO membranes to “lock” GO flakes in the adjacent layers . GO membranes can also be stabilized using cross‐linking agents, such as multivalent ions, diamine, or dyadic monomers . Via a LBL deposition technique, TMC was used to cross‐link adjacent GO flakes .…”
Section: Go‐based Membranes With Lamellar Structurementioning
confidence: 99%
“…Moreover, GO bears abundant hydrophilic groups [11], imparting great potential for broad application in water-permeating membranes [12,13]. Therefore, fabricating layered polymer/GO hybrid membrane via LbL self-assembly seems a promising strategy to obtain ultrathin, defect-free and stable active layer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, its oxidized form (graphene oxide) is used for the preparation of highly efficient pervaporation membranes with superthin selective layers. It was shown that a membrane made of graphene oxide (GO) with a thickness of 93 nm can provide a permeate flux of 2.2 kg m −2 h −1 and a separation factor of 308 in the case of pervaporative dehydration of a 80 wt % ethanol aqueous solution (70°C) [186]. In [187], in the case of dehydration of a 70 wt % aqueous solution of isopropanol (70°C), a composite membrane made of GO on a porous polyacrylonitrile substrate demonstrated a flux of 4.4 kg m −2 h −1 and a separation factor of 1160.…”
Section: Developments Of Membrane Materials For Pervaporation Processmentioning
confidence: 99%